2012
DOI: 10.1167/iovs.11-8184
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Type III Secretion System and Lens Material on Adhesion ofPseudomonas aeruginosato Contact Lenses

Abstract: CLMK isolates were mostly of cytotoxic genotype. Different genotypes did not significantly differ in its adhesion to various CL. T3SS and other adhesins are involved in bacteria-contact lens adhesion through complex interactions. Contact lens materials may also play an important role in the adherence of both genotypes of P. aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 64 publications
2
13
1
Order By: Relevance
“…Indeed, the P. aeruginosa T3SS has actually been implicated in promoting adhesion to contact lenses, as has lens exposure to artificial tear fluid. 50 Thus, the reciprocal regulation model appears to be conditional on the experimental set-up. It is unclear why there would be more robust T3SS expression in biofilms grown on contact lenses when its expression is suppressed during biofilm growth in some other circumstances, but this could relate to properties of the material, or some other variable.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the P. aeruginosa T3SS has actually been implicated in promoting adhesion to contact lenses, as has lens exposure to artificial tear fluid. 50 Thus, the reciprocal regulation model appears to be conditional on the experimental set-up. It is unclear why there would be more robust T3SS expression in biofilms grown on contact lenses when its expression is suppressed during biofilm growth in some other circumstances, but this could relate to properties of the material, or some other variable.…”
Section: Discussionmentioning
confidence: 99%
“…It would be reasonable to suppose that since P. aeruginosa invaded the deep corneal stromal, phages could not infiltrate there. P. aeruginosa are motile and produce proteolytic enzymes, such as elastase B, alkaline metalloprotease (37), protease IV (38), and P. aeruginosa small protein (39), and have a type III secretion system (40). These enzymes enable P. aeruginosa to rapidly cause keratitis and to invade deep layers.…”
Section: Discussionmentioning
confidence: 99%
“…The association of contact lens wear and cytotoxic strains has been previously demonstrated, as isolates from CLMK cases were mostly cytotoxic. 9,10 Reasons for the association of cytotoxic strains with contact lens wear need further investigation. Although the quantity of bacteria adhering to various contact lens materials was not significantly different between the two genotypes, 9 resistance of cytotoxic strains to contact lens disinfection solutions has been reported and may be one explanation for its predominance among CLMK cases.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Analysis of genotype distribution found that isolates from patients with contact lens-associated microbial keratitis (CLMK) were mostly of the cytotoxic genotype. 9,10 Although both in vitro and animal models of pseudomonal keratitis have shown different manifestations between these two types of P.…”
mentioning
confidence: 99%